Magic's most wanted - Whitesides, Tyler (Harper, an imprint of HarperCollinsPublishers, 2021)
"For Mason Mortimer Morrison, life isn't so magical. His dad was just sent to jail, his grades have been plummeting from meh to yikes, and, oh yeah, two officers from some organization called Magix just showed up to arrest him in the middle of fourth period. Talk about bad luck. Mason knows he's innocent. But in order to clear his name, he's going to need the help of a plucky Magix junior detective and a cantankerous talking bunny--and a little bit of magic."--